2002
DOI: 10.1152/ajpheart.00261.2001
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of laminar myofiber architecture to load-dependent changes in mechanics of LV myocardium

Abstract: Takayama, Yasuo, Kevin D. Costa, and James W. Covell. Contribution of laminar myofiber architecture to load-dependent changes in mechanics of LV myocardium. Am J Physiol Heart Circ Physiol 282: H1510-H1520, 2002; 10.1152/ajpheart.00261.2001.-The ventricular myocardium consists of a syncytium of myocytes organized into branching, transmurally oriented laminar sheets approximately four cells thick. When systolic deformation is expressed in an axis system determined by the anatomy of the laminar architecture, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
83
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 42 publications
10
83
0
Order By: Relevance
“…This transmural myofiber distribution has been described in many species, including humans (12), using histology (14,18,23,28) or diffusion tensor magnetic resonance imaging (4,10,25). This helical myofiber orientation is relatively preserved among different species, ranging from approximately −60° to +60° from epicardium to endocardium, with circumferential fibers at midwall, although some studies have shown some variation from apex to base (6,23,24). The present study is the first to report transmural distribution of α in the ovine heart, but our data are consistent with these previously published reports from other species.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…This transmural myofiber distribution has been described in many species, including humans (12), using histology (14,18,23,28) or diffusion tensor magnetic resonance imaging (4,10,25). This helical myofiber orientation is relatively preserved among different species, ranging from approximately −60° to +60° from epicardium to endocardium, with circumferential fibers at midwall, although some studies have shown some variation from apex to base (6,23,24). The present study is the first to report transmural distribution of α in the ovine heart, but our data are consistent with these previously published reports from other species.…”
supporting
confidence: 91%
“…The helical arrangement of the fibers may account for some of this disparity (20), but an additional important mechanism appears to be sheet deformation (19,22). Laminar shear, extension, and thinning or thickening are thought to contribute to wall thickness changes (6,7,24).Fiber orientation, which can be measured directly, has been found in several species to vary from approximately −60° at the epicardium to +60° at the endocardium (4,10,12,14,23,28). Until recently, however, sheet orientation could only be inferred indirectly from the directions of fiber and cleavage planes from three orthogonal views (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These studies established that fiber orientation was a function of transmural location, with fiber direction being predominantly longitudinal in the endocardial region; transitioning into a circumferential direction in the midwall and becoming longitudinal again over the epicardial surface. Myofiber morphology was described either based on orientation of individual fibers or as multiple myocyte 'sheet' arrangements separated by extensive 'sheet cleavage' planes (17)(18)(19)(20). Some investigators depicted the LV as a complex nested continuum where the myofibers entwined to form a mechanical and electrical syncytium (21,22).…”
Section: Myofiber Architecture Of the Left Ventriclementioning
confidence: 99%